1986
DOI: 10.1111/j.1365-2044.1986.tb12754.x
|View full text |Cite
|
Sign up to set email alerts
|

Compound sodium lactate (Hartmann's) solution. Caution: risk of clotting

Abstract: We kuve observed blood doiring in blood administration sets nhere Hurtmann 's solution ( TravenoI) has preceded blood trunsfusion. This is due 10 calcium ions (Ca' ') contained in the Hartmann's solution and is more likely to occur at 37'C. We suggest that [hi.$ porential hazard be more widely realised and that the practice cease. Key wordsComplicarions; blood clotting. Inns; calcium. Transfusion; stored blood.Hartmann's solution is frequently used as volume replacement fluid during emergency and routine surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…9,10 These standards are based on laboratory research conducted more than 20 years ago that have demonstrated that calcium-containing crystalloids could cause clotting to occur when combined with warmed blood components preserved with CPDA. 11,12 These guidelines have remained despite numerous reports that have shown that RL does not cause clotting in clinically relevant dilutions. 2,6,8,13 Blood preservatives utilize citrate to chelate calcium contained in blood products, thereby preventing activation of the clotting cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 These standards are based on laboratory research conducted more than 20 years ago that have demonstrated that calcium-containing crystalloids could cause clotting to occur when combined with warmed blood components preserved with CPDA. 11,12 These guidelines have remained despite numerous reports that have shown that RL does not cause clotting in clinically relevant dilutions. 2,6,8,13 Blood preservatives utilize citrate to chelate calcium contained in blood products, thereby preventing activation of the clotting cascade.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 These guidelines are based, in part, on research completed in the 1970s and 80s which showed that using calcium-containing crystalloids, such as RL, can cause clotting when combined with PRBC preserved with citratephosphate-dextrose-adenine (CPDA). 11,12 However, a number of studies have challenged the claim that it is unsafe to use RL to reconstitute PRBC, and to date, no study has shown RL to cause clotting in clinically relevant dilutions of PRBC to crystalloid. 2,6,8,13 It has been shown that mixtures of PRBC and crystalloid, in a ratio of 2:1 or higher, do not overwhelm the calcium-chelating ability of the citrate in the CPDA preservative solution.…”
Section: Résumémentioning
confidence: 99%